(untitled) (Materiali di Estetica. Terza serie, 2024)
The author delves into the profound connection between philosophy and architecture as explored by Fulvio Papi between 1997 and 1999. He reflects on how architectural forms and urban structures embody philosophical ideas, moving beyond technical aspects to a philosophical interpretation of space. The paper examines Papi’s interpretation of architectural elements through a philosophical lens, drawing parallels between the theories of Immanuel Kant and architectural practices. Papi’s work is portrayed as a philosophical inquiry into the ethical dimensions of architecture, emphasizing the role of architecture in shaping the collective good and enhancing communal living spaces. The discussion extends to the implications of such philosophical underpinnings in contemporary architectural and urban planning practices.